A MODERN VIEW ON PRIMARY PREVENTION OF HYPOTHYROIDISM (Western European Journal of Medicine and Medical Science, 2025)
Hypothyroidism is an endocrinological disease that manifests itself as insufficient production of thyroid hormones. There are three degrees of the disease: primary, secondary and tertiary hypothyroidism in women and men. Hypothyroidism is one of the most common diseases of the endocrine system. Despite the well-studied etiology, pathogenesis and simple diagnosis, in some cases the disease remains unrecognized for a long time, which is due to the slow increase in thyroid deficiency and, accordingly, the severity of the clinical picture. The biological action of thyroid hormones is very diverse: by activating the transcription of numerous genes, they participate in the regulation of basic physiological processes in the body, therefore their deficiency can manifest itself in a wide variety of clinical manifestations and symptoms and imitate diseases of almost all body systems